(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A rapid, sensitive, and straightforward spectrophotometric method using the MThBAP reagent has been developed to measure nickel at the trace level. Reagent was analysed using an elemental and spectral analytical technique